Effects of Topical Application of Misoprostol on Cervical Relaxation in Mares. Issue 6 (1st November 2014) - McNaughten, J; Pozor, M; Macpherson, M; Kelleman, A; Woodward, E; Troedsson, M
Contents Mares who have not delivered a foal early in life may experience limitations in cervical relaxation, primarily during oestrus. A closed cervix prevents intrauterine deposition of semen during natural breeding, may delay uterine clearance after insemination leading to intrauterine fluid accumulation in, and subsequent infertility. Therefore, a reliable pharmacological method of dilating the equine cervix would have practical application in veterinary medicine. The goal of this study was to investigate the effectiveness of topically applied, synthetic prostaglandin E1 analogue (PGE1) for stimulating dilation of the equine cervix. Ten mares in dioestrus were randomly assigned to one of two treatments in a single‐blind crossover study: (treatment) PGE1 gel (1000 mcg compounded misoprostol cream) applied topically to the external cervical os (n = 5), and (control) a vehicle cream applied topically to the external cervical os (n = 5). Transrectal palpation and ultrasonographic measurements of the cervix were performed prior to, six and 24 h post‐treatment. Digital measurements were taken, per vagina, at six and 24 h post‐treatment. Mares were monitored through the subsequent oestrous cycle for ovulation. Mares were assigned to the opposite treatment group such that each mare served as her own control (crossover). Data were analysed using parametric (split‐plot anova), as well as nonparametric (Kruskal–Wallis anova, Wilcoxon's rank‐sum test) methods. At six and 24 h there were no significant differences for tone, length, height, degree of relaxation or echotexture between control and PGE1 treated groups at the measured time points (p > 0.05). Topical cervical application of PGE1 did not induce a measurable degree of cervical relaxation under the conditions of this experiment.